Dog man : an uncommon life on a faraway mountain - Sherrill, Martha (New York : Penguin Press, 2008)
Morie Sawataishi lives a life that is radically unconventional by any standard but almost absurd in blatantly conformist Japan. Journalist Martha Sherrill provides a profound look at what it takes to be an individualist in a culture where rebels are rare. After the Japanese surrender in 1945, there were only sixteen Akita dogs left in the country. The magnificent hunting dogs had been donated to help in the war effort, or had been eaten, and their pelts used by the military to line the winter coats of the soldiers. Morie became obsessed with preventing the extinction of the breed, and he did it in a very un-Japanese way: defying convention, breaking the law, giving up the opportunity to hold prestigious engineering jobs in Tokyo, and choosing instead to take his new wife, Kitako--a sheltered sophisticate from Tokyo--to Japan's forbidding snow country to start a family.--From publisher description.
Keywords: Akita dog; Human-animal relationships